The Obligations of Entrepreneurs Providing Services by Electronic Means - Ganczar, Małgorzata (Review of European and Comparative Law, 2023)
The development of new information and communication technologies affects economic development. E-services, along with the accompanying social changes, are being implemented in almost every area of human life, and the development of information and communication technologies makes it possible to employ a number of new instruments in its various spheres (e-banking, e-commerce, e-education, etc.). Currently, the information space in the context of the provision and use of e-services includes consumers and entrepreneurs although it assigns them different rights and obligations in this area. It seems necessary to assess the impact of the implementation by entrepreneurs of obligations related to the provision of e-services and their impact on the economy and on consumer safety in online trade. Legal changes concerning the obligations imposed on entrepreneurs in that field appear periodically in response to new threats related to dynamic technological development.The publication is devoted to an analysis of the provision of on-line services and an assessment of the law, in particular with regard to fulfilling information obligations with respect to consumers in cyberspace.